Characterization And Properties Of Polypropylene/ Recycled Acrylonitrile Butadiene Rubber/ Rice Husk Powder Composites - Santiagoo, Ragunathan (2013)

(untitled)
Themoplastic elastomer composite of polypropylene (PP)/ recycled acrylonitrile butadiene rubber (NBRr)/ rice husk powder (RHP) was investigated. All test samples were prepared using Haake Rheomix Polydrive R600/ 610 internal mixer at temperature of 180°C and rotor speed of 50 rpm. The samples were later moulded using compression moulding at temperature of 180°C. The particle sizes of the RHP and NBRr used in this research were 150 - 300 μm. The composites properties were enhanced by treating the RHP using Acetic Anhydride (Ac) and ɤ-APS as a coupling agent. Mechanical and thermal properties of all treated composites were improved. The treatment with Ac increased the hydrophobic characteristic of RHP and improves its adhesion with non-polar PP/NBRr matrixes. Better properties such as tensile, thermal stability and crystallinity of composites showed by Ac treatment compared with ɤ-APS coupling agent. Matrix compatibilization techniques were also investigated by using Diglycidal ether of bisphenol A (DGEBA) and Polypropylene grafted maleic anhydride (PPMAH). The adhesion between filler and matrix was improved for both DGEBA and PPMAH. DGEBA was found to be more effective in improving the adhesion between filer and matrix. Electron beam irradiation was also evaluated to introduce cross-linking in the composites. Electron beam irradiation at 40 kGray in the presence of TMPTA (irradiation crosslink promoter) was used. Results showed that composites have highest tensile properties, gel content, thermal stability and crystallinity but lowest percentage of water absorption.